HUBUNGAN TINGKAT KECEMASAN DENGAN KEPATUHAN MELAKUKAN ANTENATAL CARE (ANC) PADA IBU HAMIL DIMASA PANDEMI COVID-19 DI WILAYAH KERJA PUSKESMAS REMBANG - Titin Rokhanah; Siti Haniyah; Etika Dewi Cahyaningrum (Melati Institute, 2022)
Many factors contributed in lack of obedience of pregnant women conducting Antenatal visits. The anxiety of getting infected by Covid-19 for both themselves and the baby was one of the contributing factor, as well as the anxiety about wether the examination was safe or not. The purpose of this study was to know the relationship between level of anxiety and obedience of pregnant women in conducting antenatal visits during covid-19 pandemic in working area of Rembang Public Health Center. This is a correlational research with time frame approach using Perinatal Anxiety Screening Scale (PASS) questionnaire. Purposive sampling is used to choose sample of the research, including 46 pregnant women live around Rembang Publich Health Center. The research, using Spearman-rank test, shows 58,7% sample are anxious about Covid-19; 58,7% are conducting antenatal visits obediently. Spearman-rank test shows p-value 0,003 (p-value). The result of this research is showing there is a relationship between level of anxiety and obedience of pregnant women in conducting antenatal visits during covid-19 pandemic in working area of Rembang Public Health Center.